The legal Consequences of Default of Parties in the Lease Agreement between PT. Kereta Api Indonesia (PT. KAI) with PT. J.Co Donuts & Coffee - Nurma Khafifah; Ana Silviana (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The development of the rental business can not be denied can experience a problem along with its development, such as the problem of default that occurred between PT. J.Co Donuts & Coffee with PT. Kereta Api Indonesia (Persero). PT. J. Co Donuts & Coffee (the plaintiff) leased assets from PT. Kereta Api Indonesia (defendant) in the form of land and buildings for a period of 5 years. After the defendant made the payment for term I, the defendant did not immediately hand over the object of lease to the plaintiff to be used as a J.Co Donuts & Coffee store so this matter was brought to court. In the decision of the Supreme Court No. 211/K/PDT/2020, the judge decided that PT. KAI has defaulted by not handing over the object of the lease to PT. J.Co Donuts & Coffee. This study aims to determine the form of default and the legal consequences of the default dispute. The method used in this legal research is a normative juridical approach. The specifications used in writing this law are descriptive analytical. While the method used is a qualitative method. The results of the study indicate that the judge has decided on this case correctly, namely that the defendant has defaulted due to an error due to negligence. Furthermore, researchers also examine the legal consequences that arise in the decision of the Supreme Court no. 211/K/PDT/2020.